2022
DOI: 10.1002/yd.20495
|View full text |Cite
|
Sign up to set email alerts
|

Why use games for leadership learning?

Abstract: Why should leadership educators trouble themselves in creating or implementing games for leadership learning? This chapter justifies the use of games as a teaching strategy in leadership education by exploring three rationales. First, games can be meaningfully tied to specific learning theories. Second, games provide motivation for learning, and finally, empirical evidence supports the use of games for leadership learning.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…Banter et al (2022) argue that games should be used in leadership education for three reasons. One, they can be connected to educational theories; two, they can be motivating (Buil et al, 2019); and three, the empirical research supports their use (Banter et al, 2022). Sierra and Rodríguez-Conde (2023) argue that active-learning strategies, like games and simulations, can help students learn management skills for four reasons.…”
Section: Gaming In Management and Leadership Educationmentioning
confidence: 99%
See 1 more Smart Citation
“…Banter et al (2022) argue that games should be used in leadership education for three reasons. One, they can be connected to educational theories; two, they can be motivating (Buil et al, 2019); and three, the empirical research supports their use (Banter et al, 2022). Sierra and Rodríguez-Conde (2023) argue that active-learning strategies, like games and simulations, can help students learn management skills for four reasons.…”
Section: Gaming In Management and Leadership Educationmentioning
confidence: 99%
“…Research has also suggested the efficacy of games and simulations in business-related skills like public economics management and strategic management (Klein et al, 1993; Loon et al, 2015; Sierra & Rodríguez-Conde, 2023). Banter et al (2022) argue that games should be used in leadership education for three reasons. One, they can be connected to educational theories; two, they can be motivating (Buil et al, 2019); and three, the empirical research supports their use (Banter et al, 2022).…”
Section: Gaming In Management and Leadership Educationmentioning
confidence: 99%